Emissions to the atmosphere by power plants in Baja California Sur, Mexico - Rivera-Cárdenas, Claudia Inés; Barrera-Huertas, Hugo A.; Valenzuela, Jaqueline; Rangel, Rodrigo; López-Zamudio, Estefanía; Carbajal-Aguilar, Cristina Carolina (Renewable Energy, Biomass & Sustainability, 2024)
Sulfur dioxide (SO2) and nitrogen dioxide (NO2) emissions to the atmosphere released by three power plants located in Baja California Sur, Mexico, were quantified using mini-DOAS instruments. In La Paz municipality, the Punta Prieta Power Plant released 65.67±77.80 tons/day of SO2 and 6.66±12.57 tons/day of NO2, while the Internal Combustion Power Plant Baja California Sur released 44.72±5.37 tons/day of SO2 and 8.27±1.72 tons/day of NO2. In the municipality of Comondú, the Internal Combustion Power Plant Agustín Olachea released 18.17±8.00 tons/day of SO2 and 0.67±0.32 tons/day of NO2. Comparisons of our measurements with emissions inventories and annual operating reports for the Punta Prieta Power Plant are in good agreement, however, we found differences for the Internal Combustion Power Plant Baja California Sur and the Internal Combustion Power Plant Agustín Olachea. Our analyses show that the Punta Prieta Power Plant has increased its SO2 and NO2 emissions between 2013 and 2022. The Internal Combustion Power Plant Baja California Sur has increased its SO2 emissions, while NO2 emissions have declined between 2013 and 2022. The Internal Combustion Power Plant Agustín Olachea has been decreasing its SO2 and NO2 emissions between 2010 and 2022, albeit in 2018, there was a considerable increase of NO2 emissions.